The AT1 Receptor Blocker Telmisartan Reduces Intestinal Mucus Thickness in Obese Mice - Nickel, Laura; Sünderhauf, Annika; Rawish, Elias; Stölting, Ines; Derer, Stefanie; Thorns, Christoph; Matschl, Urte; Othman, Alaa; Sina, Christian; Raasch, Walter (Frontiers in Pharmacology, 2022)
The angiotensin II (type 1) (AT1) receptor blocker telmisartan (TEL) is beneficial for the treatment of individuals suffering from metabolic syndrome. As we have shown that TEL has an impact on gut microbiota, we investigated here whether TEL influences gut barrier function. C57BL/6N mice were fed with chow or high-fat diet (HFD) and treated with vehicle or TEL (8 mg/kg/day). Mucus thickness was determined by immunohistochemistry. Periodic acid–Schiff staining allowed the number of goblet cells to be counted. Using western blots, qPCR, and immunohistochemistry, factors related to mucus biosynthesis (Muc2, St6galnac), proliferation (Ki-67), or necroptosis (Rip3) were measured. The influence of losartan on cell viability was determined in-vitro as solubility of TEL was too low for in-vitro experiments. Upon HFD, mice developed obesity as well as leptin and insulin resistance, which were prevented by TEL. Mucus thickness upon HFD feeding was diminished. Independent of feeding, TEL additionally reduced mucus thickness. Numbers of goblet cells were not affected by HFD feeding and TEL. St6galnac expression was increased by TEL. Rip3 was increased in TEL-treated and HFD-fed mice, while Ki-67 decreased. Cell viability was diminished by using >1 mM losartan. The anti-obese effect of TEL was associated with a decrease in mucus thickness, which was likely not related to a lower expression of Muc2 and goblet cells. A decrease in Ki-67 and increase in Rip3 indicates lower cell proliferation and necroptosis upon TEL. However, direct cell toxic effects are ruled out, as in-vivo concentrations are lower than 1 mM.